Strategy of Educational Institutions to Improve the Quality of Teachers in Digital Era - R. Andi Ahmad Gunadi; Yasin Efendi; Muh Hizbul Muflihin; Isroani, Farida (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2023)
The quality of the teacher's attitude is the skill and understanding possessed by someone related to teaching and character. This study aims to find out how the strategies and innovations of educational institutions form in improving the quality of education. This study uses qualitative research with a descriptive approach. The results of the research show that the strategy for educational institutions during a pandemic is for example the existence of a program made by the school principal. The purpose of implementing the program is to improve the quality of teachers both in normal and future times. The forms of these activities are seminars, microteaching and book review. The current digital era is a period when information is easily and quickly obtained and disseminated using digital technology. This activity has had a good impact on the quality of teachers in school institutions as evidenced by the increase in teacher quality both in personality, knowledge or socially for each teacher which also has an impact on the learning process provided by teachers during a pandemic. During a pandemic covid-19, there are several strategies and innovations carried out with the aim of improving the quality of human resources in the institution. Meanwhile, the purpose of this research is to find out the strategies and innovations that have been carried out to improve the quality of teachers during a pandemic covid-19. The implications of this research can be used as a reference for other institutions to improve the quality of teachers in any situation and condition, including during the current covid-19 pandemic in the 21st century digital era.